AI-enabled ecotourism business models for socio-economic development of local communities: An empirical study on developing smart villages in West Bengal, India - Debarati Deb (Borneo Novelty Publishing, 2026)
Purpose – This study aims to evaluate the role of AI-enabled ecotourism business models in driving socio-economic development in rural areas of West Bengal, with a focus on developing smart ecotourism villages in Jhargram and Purulia.Design/Methodology/Approach – A quantitative research design was employed using data collected from 250 respondents, including ecotourism entrepreneurs, local community members, and government personnel. The study applied reliability and validity tests, factor analysis, and Structural Equation Modeling to examine relationships among digital literacy, community participation, entrepreneurial orientation, AI adoption, and socio-economic development. Mediation analysis was conducted using bootstrapping techniques in SPSS.Findings – The results reveal that digital literacy, community participation, and entrepreneurial orientation significantly and positively influence AI adoption, with entrepreneurial orientation identified as the strongest predictor. Furthermore, AI adoption has a positive impact on socio-economic development. Mediation analysis indicates that AI adoption partially mediates the relationship between entrepreneurial orientation and socio-economic development, highlighting its strategic role in rural development pathways.Originality/Value – This study contributes to the emerging discourse on smart tourism and rural development by integrating AI adoption into ecotourism business models. It provides practical insights for policymakers and stakeholders to foster digitally empowered, community-based ecotourism initiatives that enhance economic growth and sustainability in rural destinations.